Predictors and Sequelae of Postoperative Delirium in a Geriatric Patient Population With Hip Fracture. (May 2021) - Haynes, Monique S.; Alder, Kareme D.; Toombs, Courtney; Amakiri, Ikechukwu C.; Rubin, Lee E.; Grauer, Jonathan N.
Abstract : Introduction: Postoperative delirium is common for patients with hip fracture. Predictors of postoperative delirium and its association with preexisting dementia and adverse postoperative outcomes in a geriatric hip fracture population were assessed. Methods: Patients with hip fracture aged 60 years and older were identified in the 2016 and 2017 National Surgical Quality Improvement Program Procedure Targeted Databases. Independent risk factors of postoperative delirium were identified. Associations with mortality, readmission, and revision surgery were evaluated using moderation and mediation analysis. Results: Of 18, 754 patients with hip fracture, 30.2% had preoperative dementia, 18.8% had postoperative delirium, and 8.3% had both preoperative dementia and postoperative delirium. Independent predictors of postoperative delirium were as follows: older age, male sex, higher American Society of Anesthesiologists score, dependent functional status, nongeneral anesthesia, preoperative diabetes, bleeding disorder, and preoperative dementia. Preoperative dementia and postoperative delirium each had an independent correlation with 30-day mortality (odds ratios = 2.06 and 1.92, respectively, with P < 0.001 for both). However, when both were present, those with preoperative dementia and postoperative delirium had an even higher odds of mortality based on moderation analysis (odds ratio = 2.25, P < 0.001). Readmissions and reoperations were significantly correlated with postoperative delirium, but not with preoperative dementia. The combination of preoperative dementia and postoperative delirium, however, did have compounding effects. Furthermore, a significant proportion of the total effect of preoperative dementia on mortality and readmission was accounted for by the development of postoperative delirium based on mediation analysis (medeff: 7%, P < 0.001 and medeff: 35%, P < 0.001). Discussion: Postoperative delirium is a potentially preventable postoperative adverse outcome that was seen in 18.8% of 18, 754 patients with hip fracture. Those with preoperative dementia seem to be a particularly at-risk subpopulation. Quality improvement initiatives to minimize postoperative delirium in this hip fracture population should be considered and optimized.